Influence of out-of-plane disorder formed by low-temperature sintering on carbohydrate-doped MgB2 wire. Issue 13 (September 2020) - Maeda, Minoru; Patel, Dipak; Kumakura, Hiroaki; Nishijima, Gen; Matsumoto, Akiyoshi; Kim, Su-Hun; Choi, Seyong
Abstract: Structural disorder within grains formed by carbon doping is widely known to enhance the in-field transport critical current performance of MgB2 wire. The structural formation usually requires high-temperature sintering above 600 °C due to low reactivity of the dopant. In this study, we selected a carbohydrate (malic acid) that has a low-decomposition temperature as the carbon dopant and performed low-temperature sintering (below 600 °C) to introduce greater disorder within the MgB2 grains. We revealed that the doping and low-temperature sintering process cause severe disorder, especially along the out-of-plane ( c -axis) direction. The disordered formation, in addition to the in-plane disorder combined with well-connected grains, eventually raised the in-field transport performance.